PENGARUH PERSEPSI HARGA, PENGETAHUAN PRODUK, DAN CITRA PERUSAHAAN TERHADAP NIAT BELI LAYANAN MULTI SERVIS MEREK INDIHOME - Suarjana, I Kadek; Suprapti, Ni Wayan Sri (E-Jurnal Manajemen; Vol 7 No 4 (2018), 2018)
PT Telkom is the largest telecommunication company in Indonesia that innovates by releasing new products with multi-services. It is provide s voice (phone), data (internet) and picture (IP-TV) services in a single network access known as Triple Play service. Triple Play Service is given IndiHome brand. The purpose of this study is to explain the influence of price perceptions, product knowledge, and corporate image on  intention to purchase IndiHome products. The study was conducted in Denpasar City with sample size of 100 people. Research respondents are telephone subscribers of PT. Telkom who have not used the IndiHome products yet. Data were analyzed by using multiple linear regression analysis. The results of the analysis showed that the three variables have a significant positive effect on PT Telkom’s customer intention to purchase IndiHome multi-services. Among the three variables, product knowledge has the strongest influence, followed by corporate image variable, and price perception. The results of this study have practical implications that in marketing this service, PT Telkom should be more focus on market education to improve consumer knowledge of IndiHome's services, in addition to maintaining the company's image, and keeping the price of the product affordable by potential customers.